Health-seeking behaviours of students of the University of the Third Age at Wrocław Medical University. Research results and recommendations - Żanetta Kaczmarek (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
The article presents mainly empirical but also theoretical approach. The theoretical part is limited to a definition of health-seeking behaviours, which form the basis for the undertaken empirical research. A comprehensive research was of a quantitative as well as qualitative nature. The author of the study presents selected results of quantitative research which are seeking an answer to questions: - what is a social profile of senior students attending classes at the University of the Third Age? - which health-seeking behaviours do they prefer? The research was conducted in April 2017 using methods of diagnostic survey. The results indicate differentiated actions undertaken by senior citizens in relation to healthcare and varied motivations to pursue studies in late adulthood. From the projective point of view, the results serve to optimize programs or curricular activities as the University of the Third Age at the Medical University in Wrocław is celebrating its first year of operation.